Gendered labour in the clothing and textile industry in Johannesburg: how do women employed in garment factories experience the gendered nexus of paid and unpaid labour in their daily lives? - Das, Rozeena (My University, 2023)
Women garment workers experience gendered labour both in paid garment labour and in unpaid social reproductive labour. This research explores how women employed in garment factories in Johannesburg experience the nexus of paid and unpaid labour in their daily lives. The report investigates the structure of the garment industry, the working conditions and gender relations in contemporary Johannesburg, the daily experience of women garment workers on the factory floor and in their homes, the impact of this on their emotional and physical wellbeing and lastly, how women make meaning of their and experiences of multiple roles of providers, migrants, garment workers and caregivers. Adopting a qualitative approach, this research incorporates evidence from literature, in-depth semi-structured interviews, and observations. This study argues that women’s experiences of both forms of paid and unpaid labour are not divided into separate spheres but are rather overlapping and interconnected. Thus, paid, and unpaid labour are experienced within a gendered nexus.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, School of Social Science, at the University of the Witwatersrand, Johannesburg, 2023